2015
DOI: 10.3130/aija.80.907
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF SKY FACTOR AND THE CHANGE ON IMPRESSION OF TOWNSCAPE<br>With the experiment for evaluation impression while walking

Abstract: This paper aims to clarify the component of impression of townscape while walking and to verify the effect of sky factor and the change on the components above-mentioned. The results are; (1) according to the factor analysis, "Calmness", "Openness", and "Activity" compose the impression of the city, (2) neither the relation between "Calmness" and sky factor nor change of sky factor are significant, (3) sky factor and change of it define "Openness" of the city significantly, (4) "Activity" of the city appears t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Moreover, the feelings of a person are influenced by the environment while walking. Nishio et al (2015) argued that the subjects felt open and active while walking when the SVF at the current location was higher than that at a location 10 m before the current location. The GSV images were photographed at approximately 10-m intervals.…”
Section: Noveltymentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the feelings of a person are influenced by the environment while walking. Nishio et al (2015) argued that the subjects felt open and active while walking when the SVF at the current location was higher than that at a location 10 m before the current location. The GSV images were photographed at approximately 10-m intervals.…”
Section: Noveltymentioning
confidence: 99%
“…The position relations are composed of network data, which makes it possible to calculate the change in the SVF. Nishio et al (2015) reported that the subjects felt open and active 2 in those areas of a city that had a high SVF. Moreover, the feelings of a person are influenced by the environment while walking.…”
Section: Noveltymentioning
confidence: 99%
See 2 more Smart Citations
“…The impression evaluation was obtained in field experiments for several studies on sequential evaluation. For example, Nishio and Ito (2015) clarified the component of the townscape impression while walking to verify the effect of the sky factor. 3.…”
Section: Notesmentioning
confidence: 99%